Effect of physiotherapy on polycystic ovarian syndrome and lack of research - Muzna Munir; Atif Amin Baig; Zohra Zafar (Journal of the Pakistan Medical Association, 2022)
Madam, Polycystic ovarian syndrome (PCOS) is one of the most common female endocrine disorders, with a prevalence of 5–20% in women of reproductive age.(1) A recently conducted study reported that participants having PCOS diagnosed by a physician had a higher prevalence of overweight/obese women than those that self-diagnosed with PCOS.(2) Hence PCOS is the most common condition in our community and to understand it’s characteristics and how to deal with it regarding treatment is very important. While knowing about its pathological cause, chromosomal studies of patients with PCOS have shown no consistent abnormality. It is characterized by hyperandrogenemia, chronic anovulation, and polycystic ovary morphology. So, in old days it was assumed that PCOS should be treated endocrinologically. While, a more recent report concluded that hirsute PCOS women seem to have different dietary habits and reduced physical activity than controls.(3) There are many researches on dietary habits and effects of low carbohydrate diet on women with polycystic ovarian syndrome. With advancement of knowledge everyone knows about the significance of physical activity but to find the main effective treatment or regime in terms of physical therapy is difficult to find out. A systematic review on exercises therapy in polycystic ovarian syndrome. Eight manuscripts were studied and thereafter, concluded that exercise-specific interventions in PCOS are limited.(4) The results showed that even with this limited exercise interventions, there was improvement in the symptoms specifically in ovulation and weight loss. A Meta-analysis conducted in 2018 and then again in 2019 combining both, the exercise and balanced nutrition with treatment plan of 12 to 24 weeks and observed somehow improvements on PCOS patients.(5) But concluded that according to GRADE criteria, the studies were of low quality. It also had missing standardized data regarding standard physical therapy regimes for PCOS women. Though molecular genetic studies are currently ongoing, it needs more research in this domain as there is no permanent treatment of the disease. Regarding the current studies and research, the awareness is critical so that physicians can refer their PCOS patients to a nutritionist or endocrinologist as a preventive measurement. Moreover, there are only some articles supporting exercise in PCOS. Still there is a lack of research on physiotherapy protocols and specifically physiotherapy modalities with their effect on females with PCOS which needs to be focused in future. —Continue